A STUDY OF UNSTEADY FREE CONVECTIVE FLOW OF MHD WITH CONSTANT SUCTION POROUS MEDIA (International Journal of Food and Nutritional Sciences, 2022)
Abstract: we analyzed the nonlinear unsteady MHD flow of viscous, incompressible and electrically conducting fluid past a vertical porous channel under theinfluence of thermal radiation and chemical reaction. We observed how various parameters affect the flow past an infinite vertical accelerated plate.